Blue madonna ebook - Benn, James R. (Billy Boyle World War II Mystery, 2016)
Billy Boyle, World War II US Army detective and ex-Boston cop, faces his toughest investigation yet: infiltrating enemy lines in France as the Allies invade Normandy. May 1944: Captain Billy Boyle is convicted on spurious charges of black market dealings stripped of his officer’s rank, reduced to private, and sentenced to three months’ hard labor. But Billy is given an opportunity: if he takes on the incredibly dangerous mission of investigating a set of murders at the Allies’ safe house in the French town of Chaumont, he can avoid his punishment. Parachuted in as part of a three-man team the night before the Normandy invasion, he has very little time to find the killer’s identity and lead a group escape back to England, with a whole army of foes nipping at his heels.